Adult intussusception caused by cystic lymphangioma of the colon: A rare case report - Kim, Tae Oh (Baishideng Publishing Group Co., Limited, 2006)
We experienced a case of intussusception caused by cystic lymphangioma of the colon in a 32 years old female who was admitted to our hospital for the chief complaint of bloody stool. In the colonoscopic examination, cystic mass with stalk which had smooth mucosal surface was noted at the descending colon. Abdominal ultrasonography and computed tomography revealed left colon intussusception with a multilocular cystic tumor as a leading point. Emergent operation was performed. On the histopathologic examination, the cystically dilated spaces lined by endothelium and septated by fibrous septa were present. The pathological diagnosis was cystic lymphangioma of the colon. Although intussusception due to lymphangioma in an adult are rare, it should be taken into consideration that it is possible diagnosis.